Upacara Jamuan Laut (Hame-Hame Wakambangura) pada Masyarakat Buton Tengah - Agus Agus; Abdul Rahman; La Ode Syukur (Jurusan Antropologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2024)
This study aims to determine and describe the process of implementing the banquet ceremony (Hame-hame Wakambangura) in the Central Buton community and to find out what is the object or target of the banquet in the community and community expectations on the implementation of the Hame-hame Wakambangura sea banquet ceremony. To analyze the data in this study using Marcell Mauss theory. The data collection technique used in this research is a field research technique (Field Research) using two (2) methods, namely observation (Observation) and in-depth interviews (Indeepth Interview). Data analysis was carried out using a qualitative descriptive method with an ethnographic approach. The results showed that 1).The Hame-hame Wakambangura sea banquet ceremony was held by the Wakambangura Village community as a form of commemorating the death of their only daughter (Wakambangura), so the community carried out the Hame-hame Wakambangura sea banquet ceremony. In the implementation of the ritual, it is intended to entertain (Wakambangura). has the hope that the community can be maintained such as being given safety, blessings when carrying out activities at sea and on land, and always be grateful for the provision given by Allah SWT. can also increase kinship between communities which is expected to always be preserved and also this activity can be a place for silatuhrami between the people of Wakambangura Village.